Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Komitmen Dan Intensi Turnover Di Hotel Pardede International Medan - Pandapotan Nauli Sun Siregar (Jurnal Ilmiah Akomodasi Agung, 2019)
This study aims to: Test and explain namely: the effect of culture of organizationon Commitment; The effect of Culture of Organizationon turnover intention; the effect of work satisfaction on commitment; The effect of work satisfaction on turnover intention; The effect of commitment on turnover intention; The indirect influence of Culture of Organizationon turnover intentions through commitment; The indirect effect of work satisfaction on turnover intention through commitment. Respoden as many as 109 people, all hotel employees. Data were analyzed by structural equation modeling. The results of the study are: Culture of Organizationhas a positive and not significant direct effect on Commitment; Culture of Organizationhas a positive and not significant direct effect on turnover intention; Work satisfaction has a positive and not significant direct effect on commitment; Work satisfaction has a direct negative effect and is not significant for turnover intentions; commitment has a negative and not significant direct effect on the intention to employees’ move; culture of organizationhas a negative and not significant indirect effect on turnover intention through commitment; Work satisfaction has a negative and indirect significant effect on turnover intentions through commitment.